Science in the kitchen. An innovative proposal to teach physics and chemistry in secondary education. - Nuria García Martínez; Soledad García Martínez; Pedro Andreo Martínez; Luis Almela Ruiz (Enseñanza de las Ciencias, 2018)
This paper presents an innovative didactic proposal to treat some contents related to energy and the matter changes belonging to the physics and chemistry subject of third course of Compulsory Secondary Education. Its purpose is the approach of science to the real environment of students, through an everyday activity as is cooking. The proposal aims to encourage motivation and interest in science and the elimination of possible sexist attitudes. The proposal combines three practical activities: preparation of muffins, spherifications, and cooking of meat using different energy sources; and three ICT activities: analysis of TV spots, search of energy sources in a cooking program and presentation of an energy efficient kitchen. All activities are supported by the principles of recreational science and teamwork.